Aspect-Opinion Sentiment Alignment for Cross-Domain Sentiment Analysis (Student Abstract) - Ren, Haopeng; Cai, Yi; Zeng, Yushi (Proceedings of the AAAI Conference on Artificial Intelligence, 2022)
Cross-domain sentiment analysis (SA) has recently attracted significant attention, which can effectively alleviate the problem of lacking large-scale labeled data for deep neural network based methods. However, exiting unsupervised cross-domain SA models ignore the relation between the aspect and opinion, which suffer from the sentiment transfer error problem. To solve this problem, we propose an aspect-opinion sentiment alignment SA model and extensive experiments are conducted to evaluate the effectiveness of our model.